PELATIHAN PENULISAN KARYA SASTRA BERGENRE CERITA PENDEK UNTUK MENINGKATKAN MINAT LITERASI MAHASISWA - Indra Tjahyadi; Sri Andayani; Hosnol Wafa; Adi Sutrisno; Nuril Hidayati; Sugeng Edy Mulyono; Mohammad Zamroni (COVIT (Community Service of Health), 2022)
This community service aims to increase literacy interest in students in the Surabaya and Probolinggo areas through short story writing training. The urgency of doing this community service activity is because students' interest in literacy activities is still low. The method used in this training is a tutorial method and online mentoring by utilizing the Zoom meeting application. During the training, participants received literature introduction materials, basic materials for writing short story genres, short story writing practices, and work discussions. The results of this community service activity are the ability to write short stories and the formation of student literacy interests, especially in reading literary works of the short story genre. Keywords: writing workshop, short story, literation, student